Chemical composition, vasorelaxant, antioxidant and antiplatelet effects of essential oil of Artemisia campestris L. from Oriental Morocco. Issue 1 (December 2017) - Dib, Ikram; Fauconnier, Marie-Laure; Sindic, Marianne; Belmekki, Fatima; Assaidi, Asmae; Berrabah, Mohamed; Mekhfi, Hassane; Aziz, Mohammed; Legssyer, Abdelkhaleq; Bnouham, Mohamed; Ziyyat, Abderrahim
Abstract Background Artemisia campestris L. (Asteraceae) is a medicinal herb traditionally used to treat hypertension and many other diseases. Hence, this study is aimed to analyze the essential oil ofA. campestris L (AcEO) and to investigate the antiplatelet, antioxidant effects and the mechanisms of its vasorelaxant effect. Methods The chemical composition of AcEO was elucidated using GC/MS analysis. Then, the antioxidant effect was tested on DPPH radical scavenging and on the prevention of β-carotene bleaching. The antiplatelet effect was performed on the presence of the platelet agonists: thrombin and ADP. The mechanism of action of the vasorelaxant effect was studied by using the cellular blockers specified to explore the involvement of NO/GC pathway and in the presence of calcium channels blockers and potassium channels blockers. Results AcEO is predominated by the volatiles: spathulenol, ß-eudesmol and p-cymene. The maximal antioxidant effect was obtained with the dose 2 mg/ml of AcEO. The dose 1 mg/ml of AcEO showed a maximum antiplatelet effect of, respectively 49.73% ±9.54 and 48.20% ±8.49 on thrombin and ADP. The vasorelaxation seems not to be mediated via NOS/GC pathway neither via the potassium channels. However, pretreatment with calcium channels blockers attenuated this effect, suggesting that the vasorelaxation is mediated via inhibition of L-type Ca2+ channels and the activation of SERCA pumps of reticulum plasma. Conclusion This study confirms the antioxidant, antiplatelet and vasorelaxant effects ofA.campestris L essential oil. However, the antihypertensive use of this oil should be further confirmed by the chemical fractionation and subsequent bio-guided assays.